Complementary system vs conventional trifocal intraocular lens: comparison of optical quality metrics and unwanted light distribution - Naujokaitis, Tadas; Auffarth, Gerd U.; Khoramnia, Ramin; Łabuz, Grzegorz (Journal of cataract and refractive surgery, 2023)
Purpose: - To evaluate the ARTIS Symbiose complementary intraocular lens (IOL) system, consisting of the MID and PLUS models, in comparison with a conventional trifocal IOL (AcrySof IQ PanOptix). - Setting: - The David J. Apple Center for Vision Research, Department of Ophthalmology, University of Heidelberg, Heidelberg, Germany. - Design: - Laboratory investigation. - Methods: - Modulation and phase transfer functions were obtained in polychromatic light using an optical bench setup. Simulated visual acuity (VA) values were derived from optical quality metrics weighted by neural contrast sensitivity. United States Air Force (USAF) chart images were acquired and processed. Furthermore, the light distribution beyond the center of a polychromatic point spread function was assessed. - Results: - The peak simulated VA values of ARTIS Symbiose MID were at 0 diopters (D) of defocus (−0.02 logMAR) and at −1.5 D (0.00 logMAR); of ARTIS Symbiose PLUS, they were at 0 D of defocus (−0.01 logMAR) and at −2.5 D (0.01 logMAR). AcrySof IQ PanOptix demonstrated 3 peaks: at 0 D of defocus (−0.02 logMAR), at −1.75 D (0.03 logMAR), and at −2.5 D (0.02 logMAR). The summation of USAF chart images in the simulated binocular IOL system produced a slightly better image quality at −1.0 D and −1.5 D than AcrySof IQ PanOptix. The IOLs yielded comparable light spread across the studied range except for a localized intensity spike of the ARTIS Symbiose IOLs. - Conclusions: - The complementary IOL system may yield better monocular intermediate VA compared with the conventional trifocal IOL. However, the effect of binocular summation in terms of VA and the perception of photic phenomena still needs to be investigated.
Gesehen am 15.12.2023